Creation of music learning innovation by using the Isan dialect folk songs - Bootthongtim, Thanawat (Journal of Music and Performing Arts Khon Kaen University, 2024)
This research is to create music learning by using following Orff Xylophone’s concepts to develop as an innovation to be used in music activities with songs written from traditional Isan folk songs. The objectives are as follows 1) to create and apply teaching innovations by using newly developed Orff Xylophone 2) to create an Isan folk song style for music learning activities. The participants were selected by purposive sampling method including music students from schools that cooperated with Roi Et Rajabhat University. Data was collected with qualitative research process using field data, survey, observation, interview, analyzing data from documents and presented as descriptive method. The researcher reviewed literature on music teaching concepts as well as developing a new Orff Xylophone for advantage of teaching basic music and learning activities in the classroom. The newly developed Orf xylophone is made of bamboo that can be found in local area which has the proper sound to create musical instruments. It also adjusts the size to create a variety of musical patterns especially the xylophone can remove the pieces from the track and set the remaining pieces as the required amount. Regarding the creation of folk songs, the structure of Toey Khong song and Nok Sai Bin Kam Toong song which are popular songs in Isan folk music. Four new songs were written including Toey Orff, Orff Polyphony, Orff Saon, and Orff Onson. These songs were used to teach the participants. For the newly developed xylophone, it can reduce the cost of musical instruments for instruction, and the written songs can be used for teaching and learning appropriately.